Peningkatan Peran Pemerintah Desa untuk Pengentasan Kemiskinan Ekstrem di Desa Masaingi - Usman, Rudy; Furqan, Andi Chairil; Iqbal, Muhammad; Hikmah, Nur; Ananta, Hazel Nabil; Faizal, Saskia Islamay (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: According to P3KE data, the number of households experiencing extreme poverty in Donggala Regency in 2023 reached 27,964 families. This data highlights the persistently high rate of extreme poverty in the region, including in Masaingi Village, which remains home to residents experiencing extreme poverty. Based on this, this community service activity aims to enhance the role and awareness of village government officials in efforts to alleviate extreme poverty in Siboang Village, Donggala. Methodology: This activity employs an andragogical approach, emphasizing adult learning principles that focus on intrinsic motivation and self-directed learning. The program was conducted in Masaingi Village, Donggala Regency. Results: Based on a review of the Masaingi Village Budget realization report, the village's expenditure has not complied with regulatory provisions. This activity seeks to motivate and raise awareness among Masaingi Village government officials about the importance of their role, particularly in optimizing the village fund budget to combat extreme poverty in their areas. Conclusion: Strengthening officials’ capacity and awareness is essential for regulatory compliance, effective budget management and targeted poverty alleviation. The sustainable reduction of extreme poverty requires proactive planning, transparency, and alignment of funds with community needs. Limitations: The limitations of this study lie in its focus on a local scale, making its findings and recommendations potentially less generalizable to other regions with different characteristics. Additionally, the study relies on data available at the village level, which may be influenced by the quality and completeness of the reporting from relevant parties. Contribution: This study offers a practical model for capacity building in rural governance, demonstrating how andragogy can enhance local government performance in poverty reduction.